2020
DOI: 10.1101/gad.332494.119
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral organoid and mouse models reveal a RAB39b–PI3K–mTOR pathway-dependent dysregulation of cortical development leading to macrocephaly/autism phenotypes

Abstract: Dysregulation of early neurodevelopment is implicated in macrocephaly/autism disorders. However, the mechanism underlying this dysregulation, particularly in human cells, remains poorly understood. Mutations in the small GTPase gene RAB39b are associated with X-linked macrocephaly, autism spectrum disorder (ASD), and intellectual disability. The in vivo roles of RAB39b in the brain remain unknown. We generated Rab39b knockout (KO) mice and found that they exhibited cortical neurogenesis impairment, macrocephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 70 publications
(108 reference statements)
9
83
0
Order By: Relevance
“…One recent study found that RAB39B regulates the PI3K-AKT-mTOR signaling (Zhang et al, 2020). Here we also found that phosphorylated S6 levels were increased in the hippocampus, cortex, and midbrain of Rab39b KO mice compared to WT controls ( Figure 4A and Supplementary Figure 6), corroborating an upregulation of the PI3K-AKT-mTOR signaling upon loss of RAB39B.…”
Section: Loss Of Rab39b Impairs Autophagysupporting
confidence: 87%
“…One recent study found that RAB39B regulates the PI3K-AKT-mTOR signaling (Zhang et al, 2020). Here we also found that phosphorylated S6 levels were increased in the hippocampus, cortex, and midbrain of Rab39b KO mice compared to WT controls ( Figure 4A and Supplementary Figure 6), corroborating an upregulation of the PI3K-AKT-mTOR signaling upon loss of RAB39B.…”
Section: Loss Of Rab39b Impairs Autophagysupporting
confidence: 87%
“…Importantly, our results highlight the translational potential of COs to model neurodevelopmental disorders that arise from aberrant neural network formation. To date, COs have provided critical insights into the structural etiology of several neurodevelopmental disorders, including autism ( Hou et al., 2020 ; Mariani et al., 2015 ; Papariello and Newell-Litwa, 2020 ; Wang et al., 2020 ; Zhang et al., 2020 ) and epilepsy ( Niu and Parent, 2020 ; Sun et al., 2019 ). However, the characterization of neural network activity is indispensable in several of these disorders, including epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse brain, Rab39b is expressed in cortical and hippocampal neurons, as well as in dopaminergic neurons of the substantia nigra, concordant with its association with parkinsonism and cognitive impairment in humans [ 4 ]. Rab39b knockout mice showed reduced cortical neurogenesis, macrocephaly, and autistic behaviors, similarly to patients with mutations in RAB39B [ 5 ]. The Ras-related protein Rab-39B is a small neuron-specific GTPase that contributes to synapse formation and maintenance by regulating organization and dynamics of intracellular membranes and vesicular membrane traffic [ 6 ].…”
Section: Introductionmentioning
confidence: 99%